Development of soya sticks by utilization of fenugreek seeds - Mote, Gurunath; Khade, Supriya; Udachan, Iranna; Tamboli, Firoj; Lokhande, Siddharth; Sahoo, Akshaykumar (Journal of Postharvest Technology, 2022)
The aim of present work was to develop nutritional soya sticks by incorporation of fenugreek seeds. Fenugreek seeds were incorporated in soya  sticks in the powder form. As a fenugreek seed was bitter in taste, therefore seeds were debittered by processing like soaking and germination.  Fenugreek seeds were soaked for 12hr and then germinated for 48 hr. The germinated seeds were dried and grind into powder form. Chemical  properties of raw fenugreek seeds and germinated fenugreek seeds such as moisture, ash content, fat and protein on % dry basis were found  to be 4.58%, 3.84%, 6.63%, and 23.56% and 6.36%, 3.25%, 5.70% and 23.20% respectively. The fenugreek seed powder was incorporated at  1%, 2%, 3% and 4% in soya sticks. On the basis of overall analysis, from all samples, sample contains 2% fenugreek seed powder was most  acceptable. Sen¬sory attributes like appearance, taste, flavor and overall acceptability were the quality control parameters used for soya sticks  evaluation.
Keywords: Fenugreek seed; soaking; germination; oil frying; oven baking and soya sticks